Daily standing time, dietary fiber, and intake of unsaturated fatty acids are beneficially associated with hepatic insulin sensitivity in adults with metabolic syndrome - Laine, Saara; Sjöros, Tanja; Garthwaite, Taru; Honka, Miikka-Juhani; Löyttyniemi, Eliisa; Eskola, Olli; Saarenhovi, Maria; Kallio, Petri; Koivumäki, Mikko; Vähä-Ypyä, Henri; Sievänen, Harri; Vasankari, Tommi; et al. (Frontiers in Endocrinology, 2024)
Obesity is associated with impaired glucose metabolism and hepatic insulin resistance. The aim was to investigate the associations of hepatic glucose uptake (HGU) and endogenous glucose production (EGP) to sedentary behavior (SB), physical activity (PA), cardiorespiratory fitness, dietary factors, and metabolic risk markers.Forty-four adults with metabolic syndrome (mean age 58 [SD 7] years, BMI ranging from 25-40kg/; 25 females) were included. HGU was measured by positron emission tomography during the hyperinsulinemic-euglycemic clamp. EGP was calculated by subtracting the glucose infusion rate during clamp from the glucose rate of disappearance. SB and PA were measured with hip-worn accelerometers (26 [SD3] days). Fitness was assessed by maximal bicycle ergometry with respiratory gas measurements and dietary intake of nutrients by 4-day food diaries.HGU was not associated with fitness or any of the SB or PA measures. When adjusted for sex, age, and body fat-%, HGU was associated with whole-body insulin sensitivity (β=0.58), water-insoluble dietary fiber (β=0.29), energy percent (E%) of carbohydrates (β=-0.32), saccharose (β=-0.32), mono-and polyunsaturated fatty acids (β=0. 35, β=0.41, respectively). EGP was associated with whole-body insulin sensitivity (β=-0.53), and low-density lipoprotein cholesterol [β=-0.31], and when further adjusted for accelerometry wear time, EGP was associated with standing [β=-0.43].(p-value for all < 0.05).Standing more, consuming a diet rich in fiber and unsaturated fatty acids, and a lower intake of carbohydrates, especially sugar, associate beneficially with hepatic insulin sensitivity. Habitual SB, PA, or fitness may not be the primary modulators of HGU and EGP. However, these associations need to be confirmed with intervention studies.